Executive Committee Minutes 2008-03-13 - Academic Senate:::::::::
Resolution re: Staffing Ratios in Student Counseling and Psychological Services, Constitutional Amendment for faculty referenda, Revisions to the German minor and Psychology major, Resolution on the Oath of Allegiance, AS decision to leave CSSA and support for Northern Illinois University